Pengaruh Self-efficacy dan Locus of Control terhadap Employee Performance melalui Job Satisfaction (Studi pada Karyawan UD. Karya Jati Divisi Produksi Unit 2) - Mohammad Daffa Ramadhan (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This research aims to analyze the impact of self-efficacy and locus of control on employee performance through job satisfaction. This is explanatory research with a quantitative approach. The scope of this research is identified as all the employees of UD. Karya Jati, with the number of the sample being 56 employees. That sample is obtained by using the Slovin formula. Data is collected directly from conducting interviews and distributing questionnaires to employees. The data analysis technique used Structural Equation Model Partial Least Square with software SmartPLS version 3.0. The research results show that the variable self-efficacy and locus of control in partial have had a negative and not significant impact on of employees performance, self-efficacy has a positive and significant impact on job satisfaction, locus of control has a negative and not significant impact on job satisfaction and job satisfaction has a significant impact toward employees performance. The indirect effect of self-efficacy and locus of control toward employee's performance is greater than the direct effect through job satisfaction and job satisfaction was mediated the relation between self-efficacy and locus of control toward employee's performance. This research implies that if the company wants to improve employee performance, then employee job satisfaction must be realized, increasing direct supervision and increasing salaries to maximize and increase self-efficacy.